Description of Van Hiele's geometry thinking ability in solving open ended problems in the 7E-Learning Cycle in terms of self efficacy - Asna, Alivia Nur; Soedjoko, Edy; Mariani, Scolastika (Unnes Journal of Mathematics Education, 2021)
Provision of geometry material carried out at several levels of education confirms that the burden of children's knowledge in receiving different geometry material is adjusted to the ability of children at each stage. This agrees with the theory of geometry thinking conveyed by Van Hiele. One of the constructivism learning models that is expected to be able to improve problem solving skills in students, including the 7E Learning Cycle model. The purpose of this study is (1) to describe the development of Van Hiele Geometry thinking skills in students in solving open ended problems in 7E Learning Cycle learning, and (2) describe the Van Hiele Geometry thinking skills of students in solving Open Ended problems in terms of Self Efficacy in learning 7E Learning Cycle. The population in this study were students of class IX Junior High Schoolof 2 Kudus. Sampling was done by using purposive sampling technique, 6 subjects were selected, with 2 subjects for low self efficacy, 2 subjects for medium self efficacy and 2 high self efficacy subjects from class IX A as the experimental class.